Low-cost wireless power efficiency optimization of the NFC tag through switchable receiver antenna. Issue 2 (25th April 2018) - Zhao, Yi; Li, Huaye; Naderiparizi, Saman; Parks, Aaron; Smith, Joshua R.
Abstract : Near-field communication (NFC) readers, ubiquitously embedded in smartphones and other infrastructures can wirelessly deliver mW-level power to NFC tags. Our previous work NFC-wireless identification and sensing platform (WISP) proves that the generated NFC signal from an NFC enabled phone can power a tag (NFC-WISP) with display and sensing capabilities in addition to identification. However, accurately aligning and placing the NFC tag's antenna to ensure the high power delivery efficiency and communication performance is very challenging for the users. In addition, the performance of the NFC tag is not only range and alignment sensitive but also is a function of its run-time load impedance. This makes the execution of power-hungry tasks on an NFC tag (like the NFC-WISP) very challenging. Therefore, we explore a low-cost tag antenna design to achieve higher power delivered to the load (PDL) by utilizing two different antenna configurations (2-coil/3-coil). The two types of antenna configurations can be used to dynamically adapt to the requirements of varied range, alignment and load impedance in real-time, therefore, we achieve continuous high PDL and reliable communication. With the proposed method, we can, for example, turn a semi-passive NFC-WISP into a passive display tag in which an embedded 2.7″ E-ink screen can be updated robustly by a tapped NFC reader (e.g. an NFC-enable cell-phone) over a 3 seconds and within 1.5cm range.